Vitamin D Suppression of Endoplasmic Reticulum Stress Promotes an Antiatherogenic Monocyte/Macrophage Phenotype in Type 2 Diabetic Patients - Riek, Amy E. (American Society for Biochemistry and Molecular Biology, 2012)
Cardiovascular disease is the leading cause of morbidity/mortality in patients with type 2 diabetes mellitus (T2DM), but there is a lack of knowledge about the mechanism(s) of increased atherosclerosis in these patients. In patients with T2DM, the prevalence of 25-hydroxy vitamin D (25(OH)D) deficiency is almost twice that for nondiabetics and doubles the relative risk of developing cardiovascular disease compared with diabetic patients with normal 25(OH)D. We tested the hypothesis that monocytes from vitamin D-deficient subjects will have a proatherogenic phenotype compared with vitamin D-sufficient subjects in 43 patients with T2DM. Serum 25(OH)D level inversely correlated with monocyte adhesion to endothelial cells even after adjustment for demographic and comorbidity characteristics. Vitamin D-sufficient patients (≥30 ng/ml 25(OH)D) had lower monocyte endoplasmic reticulum (ER) stress, a predominance of M1 over M2 macrophage membrane receptors, and decreased mRNA expression of monocyte adhesion molecules PSGL-1, β(1)-integrin, and β(2)-integrin compared with patients with 25(OH)D levels of <30 ng/ml. In vitamin D-deficient macrophages, activation of ER stress increased adhesion and adhesion molecule expression and induced an M2-predominant phenotype. Moreover, adding 1,25(OH)(2)D(3) to vitamin D-deficient macrophages shifted their phenotype toward an M1-predominant phenotype with suppressed adhesion. Conversely, deletion of the vitamin D receptor in macrophages from diabetic patients activated ER stress, accelerated adhesion, and increased adhesion molecule expression. The absence of ER stress protein CCAAT enhancer-binding protein homologous protein suppressed monocyte adhesion, adhesion molecule expression, and the M2-predominant phenotype induced by vitamin D deficiency. Thus, vitamin D is a natural ER stress reliever that induced an antiatherogenic monocyte/macrophage phenotype.